If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 = 3y + 9 Reorder the terms: 13 = 9 + 3y Solving 13 = 9 + 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. 13 + -3y = 9 + 3y + -3y Combine like terms: 3y + -3y = 0 13 + -3y = 9 + 0 13 + -3y = 9 Add '-13' to each side of the equation. 13 + -13 + -3y = 9 + -13 Combine like terms: 13 + -13 = 0 0 + -3y = 9 + -13 -3y = 9 + -13 Combine like terms: 9 + -13 = -4 -3y = -4 Divide each side by '-3'. y = 1.333333333 Simplifying y = 1.333333333
| 3m-m=3 | | 11-4p=26-9p | | 7x-12=4x+30 | | 2(8n-10)=9n+8 | | 5.4a-12.7=1.3-1.6a | | -5=13-3M | | 2x^2-20x-78=0 | | -7+3x=-73 | | 10*x-2*5=16 | | -3(+5)=3(x-1) | | -3+4x=-35 | | 5x^6=-320 | | 5m+3=9-4m | | 5x+6=2-3x | | 2(2y+7)-9y=-2(3-5y)+5 | | 10+6x=46 | | 2x+7=14+5x | | 16=3x+3 | | 100/5/2*5=16 | | 8x+9=2(7x-6) | | 13*4-22/11+5*x=75 | | 40+3x=-20 | | (3+w)w+w+(3+w)=24 | | 2x-5=34+x | | 7(c-9)=9(2c-8)+4 | | iman=5 | | 3x^2-6x-5=4 | | 12-5u= | | 3x^4-4x^2-1=0 | | lg(2x+40)=1.75 | | 8x+3(20-x)=125 | | 57.50-8=49.50 |